Cost-effectiveness analysis of first-line combination chemotherapy regimens for metastatic pancreatic cancer and evidence-based pricing strategy of liposomal irinotecan in China - Xiang, Zuojuan; Ma, Ling; Li, Zhengxiong; Fu, Yingzhou; Pan, Yong (Frontiers in Pharmacology, 2024)
BackgroundThe phase III NAPOLI-3 trial, which upgraded FOLFIRINOX (leucovorin, fluorouracil, irinotecan and oxaliplatin) to NALIRIFOX (liposomal irinotecan, oxaliplatin, leucovorin, and fluorouracil), demonstrated the superiority of NALIRIFOX over GEMNABP (gemcitabine and nab-paclitaxel) as the first-line treatment for metastatic pancreatic ductal adenocarcinoma. The purpose of this study was to assess the cost-effectiveness of NALIRIFOX, FOLFIRINOX, and GEMNABP, and to simulate the price of liposomal irinotecan at which NALIRIFOX could achieve cost-effectiveness.MethodsA partitioned survival model was performed to evaluate the cost-effectiveness of NALIRIFOX, FOLFIRINOX and GEMNABP from the perspective of the Chinese healthcare system. Survival data was obtained from a recently published network meta-analysis (NMA). Drug prices were collected from the database of the Hunan Province Drug and Medical Consumables Procurement Management Subsystem. Other cost and utility values were sourced from established literature. Cumulative costs, LYs (life-years), quality-adjusted life years (QALYs), incremental cost-effectiveness ratios (ICERs), net monetary benefits (NMBs) and incremental net monetary benefits (INMBs) were the main outputs. Furthermore, the variations in ICER were analyzed as the price of liposomal irinotecan gradually decreased when comparing NALIRIFOX with FOLFIRINOX or GEMNABP. The robustness of the model was assessed by sensitivity analysis and scenario analysis.ResultsAt the willingness-to-pay (WTP) threshold of $38,223.34, GEMNABP was the favored treatment. NALIRIFOX was associated with the highest LYs, QALYs, and cost. The cost-effectiveness of NALIRIFOX would be obtained if the price of liposomal irinotecan was less than $3.36/mg and $2.08/mg compared to FOLFIRINOX and GEMNABP, respectively, without considering the patient assistance program (PAP). Sensitivity analysis and scenario analysis revealed that the results of the model were stable.ConclusionFrom an economic standpoint, GEMNABP represents the favored choice in the prevailing market conditions among these three first-line combination chemotherapy regimens. The price simulation of liposomal irinotecan conducted in this study could provide valuable evidence for healthcare decision-making. Further evidence regarding the budget impact is still needed.